Molecular phylogeny of the tribe Torini Karaman, 1971 (Actinopterygii: Cypriniformes) from the Middle East and North Africa - Borkenhagen, Kai (Zootaxa, 2017)
Freshwater fishes of the cyprinid tribe Torini are widespread in Africa the Middle East and Indomalaya. The relationships of Middle-Eastern Torini are analysed based on mitochondrial markers (Cyt b, ND4) of the majority of relevant species. I present a larely well resolved phylogeny, which confirms the validity of the morphologically defined genera Arabibarbus, Carasobarbus, Mesopotamichthys and Pterocapoeta. The Torini originated in Indomalaya and colonised Africa via the Middle East. Morocco was colonised two times independently, first from sub-Saharan Africa and secondly along the southern margin of the Mediterranean Sea. The Tigris–Euphrates system is an important crossroad for the colonisation of the Jordan River, the Orontes River and the watercourses of the Arabian Peninsula by freshwater fishes. The Jordan lost its connection to the Euphrates earlier than the Orontes. The Arabian Peninsula was colonised from the Tigris–Euphrates system in at least two independent events.